A new species of Amphiascoides Nicholls, 1941 (Crustacea, Copepoda, Harpacticoida) from the Caribbean coast of Mexico - Suárez-Morales, Eduardo; Avilés-Torres, Silvia (Zootaxa, 2003)
During the analysis of the stomach contents of the hardhead silverside Atherinomorus stipes (Müller & Troschel, 1847), a tropical littoral-feeding coastal fish collected in the Yucatan Peninsula, several specimens of harpacticoid copepods were recovered. Among those that were in condition for taxonomicstudy, was an undescribed species of the miraciid genus Amphiascoides. The new species, A. walteri, is described based on a group of female specimens. It can be distinguished by a combination of characters not found in any other of the 20 species known to be contained in this genus: aesthetasc on the fourth antennular segment not reaching the last segment of the antennule, 7 setae on the third exopodal segment of the fourth swimming leg, a female fifth leg exopod over 2.3 times longer than wide, a fifth leg baseoendopod not reaching half the length of the exopod; additional differences were found with respect to the female sixth legs. The number of recognized species of the genus rises to 21; their general distribution is also presented herein. The new species represents the third species of the genus known from the Neotropical region and it is the first record of the genus in Mexican waters.